117 Tricuspid valve annular dynamics in normal vs dilated right hearts; a 3D TOE Study. (9th June 2011) - Ring, L; Rana, B; Rusk, R A
Abstract : Background: The tricuspid valve annulus (TVA) is a complex three dimensional structure that is non-planar, and is incompletely understood. The dynamics of the normal TVA has not been described in any significant detail, nor has the impact of abnormal right hearts on the TVA been described. This study was designed to assess the feasibility of assessing the TVA throughout the cardiac cycle using 3D transoesophageal echo (TOE). Methods: 20 patients were included, divided into 2 groups: normal right hearts (n=10), and dilated right hearts (n=10). 3D zoom images of the TVA were acquired using an iE33 imaging platform and X7-2t transducer (Phillips, Andover, Massachusetts, USA). Antero-posterior (AP) diameter, septo-lateral (SL) diameter, area and height were measured at 6 points of the cardiac cycle adapting commercially available software designed for assessing the mitral valve (MVQ, Phillips). The eccentricity ratio was calculated as AP/SL. Results: TVA area decreases during systole in both groups, and is greatest in mid-diastole. The area is significantly larger in the abnormal group (mean 1795 mm 2 abnormal vs 1204 mm 2 normal; p<0.01). The SL diameter increased more in the abnormal group, resulting in a circular orifice and lower eccentricity ratio throughout the cycle (mean 0.91 abnormal v 1.22 normal; p<0.01, see graph). Annular height is similar in both groups but has an upward trend in systole in normals and reduces in abnormals, reaching significance at end systole (6.7 mm vs 4.9 mm; p=0.046). Conclusions: In patients with abnormal right hearts, the TVA dilates in a septo-lateral direction, resulting in a more circular orifice. The dynamic changes of the TVA are similar in dilated vs normal right hearts, with the exception of annular height. This pilot study suggests that 3D TOE provides insight into understanding tricuspid annular dynamics.